Beyond the eye: making block-based programming languages accessible to visually impaired people - Rezende, Sandro M.; Perdigão, Luciana T.; Silva, Jociene M. M.; Guarda, Graziela F.; Pinto, Sergio C. C. S.; Fernandes, Edicléa M.; Teixeira, Gerlinde A. P. B. (Anais do Workshop de Pensamento Computacional e Inclusão (WPCI); 2022: Anais do I Workshop de Pensamento Computacional e InclusãoDO - 10.5753/wpci.2022.226547, 2022)
The aim of this work is to present a literature review concerning the accessibility of block-based programming languages and environments for people with visual impairments. The results show that the most popular block-based languages are built on graphical features that are not accessible for visually impaired people. However, some languages have been developed with the visually impaired learner in mind. We conclude that, in addition to the development of specific languages, other kinds of efforts have been made for the creation of accessible block-based programming environments.